Financial inclusion and firms growth in manufacturing sector: A threshold regression analysis in selected ASEAN countries - Rosmah Nizam; Zulkefly Abdul Karim; Tamat Sarmidi; Aisyah Abdul Rahman (Economies, 2020)
This paper examines the effect of financial inclusion on the firm growth of the manufacturing sector (513 firms) in selected ASEAN countries (Malaysia, Philippines, and Vietnam) using a cross-section threshold estimation technique. The levels of financial inclusion across firms were measured based on the distribution of financial services (access to credit). The main findings revealed that there is a non-monotonic effect of financial inclusion on the firm's growth. These findings show that the impact of financial inclusion on firm growth in the manufacturing sector is significantly positive below a threshold point, and turns to significantly negative after a certain threshold point has been reached. These new findings suggest that manufacturing firm owners and banking institutions should deepen their financial inclusion efforts, and limit the distribution of credit access within the optimum value or threshold level in promoting the growth of the firm.
Keywords: O04; O47; C31; C18; C50; 330; financial inclusion; firm growth; threshold estimation